Nadczłowiek — najwyższy autorytet i prawodawca - Baranowska, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The article provides an attempt at reconstruction of Nietzsche’s views concerning the character of Overman’s power in the future society. The most basic issue is to define who Overman is. According to Nietzsche, contemporary human being exhibits a tendency towards nihilism, mainly due to decadent values which he embraces. In order to renounce nihilism, it is imperative to revaluate all the values which, until now, had determined our humanity. In other words it is necessary to overcome our humanity. Only the strongest individuals who are capable of multiplying their will to power which is the essence of reality are able to achieve this purpose. It is them who, after this moment of purification when they start constructing new values, can become Overmen i.e. true and authentic creators. Since only a minority of human beings can overcome their humanity, it is them who will wield power in a hierarchical society of the future. The article presents the analysis of this authority, meaning the question of its possessor, source, legitimacy, sovereignty and scope. In other words it deals with the issue of role and function of Overman’s power in society. These elements are indispensable in order to fi nd an answer to the question whether political power as projected by Nietzsche is of authoritarian or maybe totalitarian character. This question is quite often asked because of the philosopher’s criticism towards democratic rule and also because of Nazi recognition – though unsubstantiated – of Nietzsche as a precursor of their ideological outlook. It appears that the in-depth comparison of the character of Overman’s power with the features of authoritarianism or totalitarianism justifies the conclusion that Nietzsche’s vision is not at all similar to axiology embodied in those systems. The only resemblance in this respect can be found in the emphasis placed on the absolute character of Overman’s authority over society. Nevertheless this authority – according to Nietzsche – is a creation of values the purpose of which is development and enhancement of will to power and not repression of individuals.
Keywords: Nietzsche, Friedrich (1844-1900); Overman; authoritarianism; totalitarianism